Do the incandescent and led lights alter the biology of Aedes aegypti (Diptera: Culicidae)? - Wan Fatma Zuharah,; Liew, Yan Hui; Nik Fadzly, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The invention of the light bulb brings darkness into the light in the sky. This study aims to understand the impact of light types and exposure duration on altering the biology and development of Aedes aegypti. A total of 100 eggs in triplicate were exposed to two types of light: light produced by the light-emitting diode (LED) light bulb and the incandescent light bulb. The eggs were exposed to the light at three different duration (1) 12h light: 12 h dark, (2) 6h light: 18h dark, and (3) 1h light: 23h dark. The results revealed that the hatching rate of Ae. aegypti eggs increased in mosquitoes exposed to incandescent light with a longer duration of light exposure, but not significantly different (p>0.05). The same pattern has been observed for mosquitoes exposed to the LED light bulb. However, when comparing the 6h light: 18h dark, a significantly more hatching rate occurred after exposure to LED light (p=0.016). More days was required by Ae. aegypti to reach adulthood when reared under incandescent light at 12D: 12L duration than LED light (p<0.05). Exposure to both types of light did not seem to alter the sex ratio of adult mosquitoes emerged. In conclusion, neither incandescent nor LED light has a significant effect in altering the biology and development of Ae. aegypti.